Stability analysis of mine overburden dump and improvement by soil nailing. (2022) - Rajhans, Puja; Ekbote, Anupkumar G; Bhatt, Gaurav
Abstract: The conventional method for carrying out stability analysis of dump involving Limit Equilibrium Method (LEM), when compared with the strength reduction method (SRM) using Finite Element Method (FEM) approach, resulted in overprediction of the factor of safety (FoS). In the present study, slope stability analysis of external overburden dump in Sonepur Bazari opencast mine has been carried out. Morgenstern Price method using constant inter-slice force function conducts the analysis of LEM using Geo-studio Slope/w, and the FEM analysis is carried out using the PLAXIS 2D 2016. The study is carried out to assess the effect of the dump's friction angle, slope angle, height, and bench configuration. Further, the analysis considering the soil nailing is also conducted by optimizing the number of nails, the distance between nails, length of the nails, nail inclination angle. The stability analysis found that the dump is in a critical state (FoS = 0.92) with a circular failure surface. The optimum slope angle is found to be 30˚. It is observed that LEM cannot detect the increased localized stress concentration at the bench edge. Reinforcement of the dump using the soil nailing technique has affected the dump stability substantially, with an increase of 11% in the FoS; however, the effect of nail orientation on dump stability was less pronounced. Further bench provision to the dump slope increases the FoS by 27%, 21% and 19%, considering the total height of 60 m, 80 m and 100 m, respectively.